Sistem Informasi Install Driver Dan Troubleshooting Produk Berbasis Web Di PT. Axis Media - Nilovar Asyiah (Jurnal Ilmu Komputer, 2024)
Every product, especially new hardware, before use must require special procedures in advance in order to be operated.To be able to connect the computer with the hardware in need of a software so that later the hardware is operated easily. Within a certain period of hardware there is usually a problem and product damage that often arises. In order to overcome these obstacles or damage in need of knowledge or correct procedures for hardware that can be repaired and reusable. because of the large number of products it requires a lot of software drivers, and stock software is on the Compact Disk or CD that takes time to look for it and for troubleshooting product problems, often the support team in response to complaints from customers difficulties finding solutions spontaneously because of problems product improvements are usually handled by technicians, so sometimes the support team find out on the internet first or ask with a technician directly. The purpose of this study is the search for drivers, how to install drivers and troubleshooting articles can easily be in, because there is already a container so that drivers live to download without having to search first. As for the procedure of installing the driver or how to solve the troubleshooting of the product just do the title problem and then the article will appear, so in answering questions from customers quickly and assist technicians in completing the repair hardware.